The Effectiveness of Quizizz Toward Students’ Vocabulary Mastery at The Seventh Grade of SMPN 4 Padang Panjang - Reflinda, Reflinda; Putri, Deva Monika; Roza, Veni; Melani , Melyann (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study was to determine the effectiveness of using Quizizz on the vocabulary mastery of seventh-grade students at SMPN 4 Padang Panjang. This study used a quantitative descriptive method with two classes (VII.1 and VII.2) as samples, consisting of 64 students. The used in this study consisted of vocabulary mastery test results. The research results indicated that Quizizz was effective for students' vocabulary mastery, with an overall score categorized as high/good at 88. Both classes showed an improvement of +0.1 before and after Quizizz implementation. Based on this increase in vocabulary mastery test scores (+0.1) and average post-test scores above 80, Quizizz had a positive impact on students' vocabulary mastery. Although before and after test vocabulary scores were categorized as low, they demonstrated score stability that students could maintain, along with a consistent improvement. It can be concluded that Quizizz is an effective learning medium that enhances students' activity, participation, and motivation in vocabulary mastery.